2020
DOI: 10.1038/s41396-019-0578-6
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory mutations modulate the competitiveness and dynamics of plasmid-mediated colistin resistance in Escherichia coli clones

Abstract: The emergence of mobile colistin resistance (mcr) threatens to undermine the clinical efficacy of the last antibiotic that can be used to treat serious infections caused by Gram-negative pathogens. Here we measure the fitness cost of a newly discovered MCR-3 using in vitro growth and competition assays. mcr-3 expression confers a lower fitness cost than mcr-1, as determined by competitive ability and cell viability. Consistent with these findings, plasmids carrying mcr-3 have higher stability than mcr-1 plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 13 publications
1
49
0
1
Order By: Relevance
“…The mcr - 3.1 gene was identified predominantly in the IncHI2 plasmid, which is associated with the spread of MDR, including β-lactams and quinolones [ 14 , 21 ]. Agreeing with Li et al [ 16 ], the mcr - 3.5 genes belonged to IncP plasmid. The less frequent plasmid replicon types in our study, such as IncI1-α, IncM, IncN, and IncP, were reported to co-harbor genes resistant to aminoglycosides, β-lactams, quinolones, and tetracyclines in Enterobacteriaceae [ 17 , 21 , 22 ].…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The mcr - 3.1 gene was identified predominantly in the IncHI2 plasmid, which is associated with the spread of MDR, including β-lactams and quinolones [ 14 , 21 ]. Agreeing with Li et al [ 16 ], the mcr - 3.5 genes belonged to IncP plasmid. The less frequent plasmid replicon types in our study, such as IncI1-α, IncM, IncN, and IncP, were reported to co-harbor genes resistant to aminoglycosides, β-lactams, quinolones, and tetracyclines in Enterobacteriaceae [ 17 , 21 , 22 ].…”
Section: Resultssupporting
confidence: 64%
“…In addition, Fukuda et al [ 13 ] identified the mcr-3 gene in 8% of E. coli isolated from diseased pigs in Japan. mcr-3- carrying plasmids can stably persist by lowering fitness cost [ 16 ], suggesting careful monitoring of the mcr-3 gene in Korean livestock.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 8, left column (experiment with fixed mutation frequency for plasmid fitness cost compensation of 10 −5 ) shows that the number of plasmid cost-compensated E. coli is lower when the cost of carrying the plasmid increases (given that bacteria replicate more slowly); however, cost-compensated bacteria (green line) outpace the non-compensated bacteria (red line) much earlier. Thus, the expected benefit of mutational compensation is proportional to the fitness cost imposed by the plasmid (37). By increasing the plasmid fitness cost, the replication of bacteria is impaired, thus possibly reducing the population size and the possibility of obtaining compensatory mutations.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, this might explain why E. coli isolates harboring plasmids with extended-spectrum β-lactamases have increased mutation frequencies (57). As proof of this concept, the benefit for cost-compensated strains (and for K. pneumoniae ) becomes clear in a hypothetical scenario containing strains with a 10 −3 mutation frequency (37).…”
Section: Discussionmentioning
confidence: 98%